Complete Genome Sequence of Amycolatopsis mediterranei S699 Based on De Novo Assembly via a Combinatorial Sequencing Strategy - Tang, Biao (American Society for Microbiology, 2012)
The genome of Amycolatopsis mediterranei S699 was resequenced and assembled de novo. By comparing the sequences of S699 previously released and that of A. mediterranei U32, about 10 kb of major indels was found to differ between the two S699 genomes, and the differences are likely attributable to their different assembly strategies.